The 9th International Conference on Sustainable Development (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The International Conference on Sustainable Development (ICSD) was held virtually on September 20-21, 2021, with the conference theme “Research for Impact: A Sustainable and Inclusive Planet.” ICSD provides a forum for academia, government, civil society, UN agencies, and the private sector to come together to share practical solutions to achieve Sustainable Development Goals (SDGs). The two-day conference hosted 49 different sessions across multiple time zones to accommodate the global audience, with 204 oral presenters, 239 poster presenters, and 977 total authors.